Hukum Islam dan Hukum di Indonesia tentang Pernikahan Beda Agama - Hidayat, M. Taufiq; Nu'man, Ali; Yamin, Ashabul; Hafidh, Hafidh; Saiban, Kasuwi (Lembaga Yasin AlSys, 2023)
This research aims to examine the perspective of Islamic law regarding interfaith marriage. The method used is qualitative, with a comparative approach. In the study of Islamic law, interfaith marriages are classified into three categories: marriages between Muslim men and polytheistic women; Muslim man's marriage to ahlulkitab woman; and the marriage of Muslim women to non-Muslim men. Regulatively, interfaith marriages in Indonesia do not have legal force, because Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law as positive law has prohibited interfaith marriages. Therefore, the Office of Religious Affairs and the Civil Registry will not carry out administrative records of interfaith marriages.